ANALYSIS OF COMBINED LAND AND SATELLITE ALTIMETRY DERIVED BOUGUER ANOMALY DATA FOR POTENTIAL HYDROCARBON AREA IDENTIFICATION (CASE STUDY: B-FIELD, SOUTH TIMOR) - CHRISTOFEL YOSHUA (NIM: 22315308), PANGERAN
The application of satellite altimetry in shallow marine areas is very useful in different geophysical applications. Altimetry derived gravity – bouguer anomaly computation is an important aspect of geophysical satellite altimetry application. This research conducts data computations and merging of complete bouguer anomaly data from terrestrial survey and DNSC08 & Sandwell satellite altimetry derived marine gravity model to produce a coherent gravity surface that encompasses the research area. The North Betano Structure that is situated in area-B of Timor Island is an anticline structure with hydrocarbon prospectivity based on gravity interpretation. The B-1 well that is drilled with a total depth of 784m did not found any potential reservoir rocks while the B-2 well that is drilled with a total depth of 1532m found a potential reservoir in the form of a limestone interval and also oil shows during drilling. The geological modelling results shows that the B-2 well is drilled offstructure and missed the structural high that is being represented as a gravity high on the model. The method that is being used in this research is proven to be effective to identify potential hydrocarbon areas for exploration and further geological and geophysical studies. The complete bouguer anomaly distribution from the Bullard corrections computations onbtained form the DNSC08 derived marine gravity model is in the range of -34.390 ~ 267.925 mGal, while the Sandwell derived marine gravity model is in the range of -32.446 ~ 266.967. The mean and RMSE value of difference between the DNSC08 and Sandwell model is 0.036 ± 2.351 mGal. This value indicates that the gravity distribution of both models are relatively similar. This proves that satellite-based marine gravity model can be effectively used to geophysical analysis applications.